2013
DOI: 10.1037/a0034568
|View full text |Cite
|
Sign up to set email alerts
|

Graduate student dissonance: Graduate students of color in a U. S. research university.

Abstract: This qualitative investigation examined the experiences of a population of graduate students-graduate students of color-in a U. S. research university (a) to indicate reasons for their dilemmas, ambiguities, and decisions about choosing an academic career, and (b) to identify the practices of one research university's graduate programs that have considerable influence upon graduate students' decisions about pursuing an academic career. For graduate students of color, professional and social identity alignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Second, the current sample was primarily White, making it difficult to fully represent the overall CE doctoral student population. Given that minority students face considerable challenges in their graduate programs (Chan, Yeh, & Krumboltz, ; Clark, Mercer, Zeiger‐Hill, & Dufrene, ; Levin, Jaeger, & Haley, ; Nelson & Jackson, ), our results may not be generalizable to minority CE doctoral students. Future studies should be more purposeful in obtaining diverse samples and could focus on comparing factors involved in researcher development between White and non‐White CE doctoral students.…”
Section: Discussionmentioning
confidence: 91%
“…Second, the current sample was primarily White, making it difficult to fully represent the overall CE doctoral student population. Given that minority students face considerable challenges in their graduate programs (Chan, Yeh, & Krumboltz, ; Clark, Mercer, Zeiger‐Hill, & Dufrene, ; Levin, Jaeger, & Haley, ; Nelson & Jackson, ), our results may not be generalizable to minority CE doctoral students. Future studies should be more purposeful in obtaining diverse samples and could focus on comparing factors involved in researcher development between White and non‐White CE doctoral students.…”
Section: Discussionmentioning
confidence: 91%
“…An important element of program value is socialization to professional identity and field-of-practice, supporting students' identity development, through out-of-class as well as in-class experiences (Liddell, Wilson, Pasquesi, Hirschy, & Boyle, 2014). Various subgroups, such as non-traditional students, who return for advanced degrees after years in professional practice, and students in racial and ethnic minority subgroups, have been identified as having particular challenges with dissonance and identity development in the graduate experience (e.g., Levin, Jaeger, & Haley, 2013;McCoy & Gardner, 2011;Peters & Daly, 2013;Rayner, Lord, Parr, & Sharkey, 2015).…”
Section: Competence and Identity Development With Degree Value In Gramentioning
confidence: 99%
“…Maton et al (2011) reported that graduate students from underrepresented populations may also experience barriers finding a fit with graduate programs. To identify opportunities that may lead to success, Levin, Jaeger, and Haley (2013) found that minority students' sense of harmony with a particular graduate program impacted their selection of and satisfaction with the program. Costello (2005) defined these concepts as the degree to which a students' personal identity is congruent with the identity of a graduate program (i.e., students' perception of faculty attitudes toward minority students).…”
Section: Journal Of Counselor Preparation and Supervision Volume 9 mentioning
confidence: 99%
“…According to Costello (2005), the greater incongruence between personal identity and the values of faculty, the less successful the student may fit with the graduate program. Levin et al (2013) found that the concept of identity congruence also applies to the career choices and quality of experiences of minority students. If a minority student believes their career choice was not supported by the program faculty, then they may feel disconnected and less likely perceive they fit.…”
Section: Journal Of Counselor Preparation and Supervision Volume 9 mentioning
confidence: 99%